2010
DOI: 10.1021/jp910203y
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 1-Nitronaphthalene: A Potential Source of Singlet Oxygen and Radical Species in Atmospheric Waters

Abstract: Abstract1-Nitronaphthalene (1NN) was used as a model of nitro-PAHs to investigate photosensitized reactions in aqueous solution in the presence of oxygen and halides. Laser Flash Photolysis (LFP) was employed to investigate electron transfer between halide anions and the triplet state of 1NN, leading to the formation of dihalogen radical anions (X 2 •-) in solution. The experiments were performed in the absence or presence of oxygen, showing a bimolecular quenching rate constant for the triplet state of 1NN ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 47 publications
3
52
1
Order By: Relevance
“…If molecular oxygen can also scavenge one or more of the radicals formed in 1-nitronaphthalene and 2-methyl-1-nitronaphthalene, then this would explain part or all of the reduction in the photodegradation yield reported in Table 1 under aerobic conditions. For instance, recent experiments in aqueous solutions have shown that the radical anion of 1-nitronaphthalene can be scavenged by molecular oxygen [69]. Clearly, however, the experiments presented herein cannot prove or rule out the participation of the triplet state in the photoreactivity of these nitronaphthalene derivatives or the direct scavenging by molecular oxygen of one or more of the radical species proposed in Scheme 1.…”
Section: Photodegradation Rates and Quantum Yields In Nitronaphthalencontrasting
confidence: 59%
“…If molecular oxygen can also scavenge one or more of the radicals formed in 1-nitronaphthalene and 2-methyl-1-nitronaphthalene, then this would explain part or all of the reduction in the photodegradation yield reported in Table 1 under aerobic conditions. For instance, recent experiments in aqueous solutions have shown that the radical anion of 1-nitronaphthalene can be scavenged by molecular oxygen [69]. Clearly, however, the experiments presented herein cannot prove or rule out the participation of the triplet state in the photoreactivity of these nitronaphthalene derivatives or the direct scavenging by molecular oxygen of one or more of the radical species proposed in Scheme 1.…”
Section: Photodegradation Rates and Quantum Yields In Nitronaphthalencontrasting
confidence: 59%
“…Our results suggest that other cations and anions present in seawater are responsible for a competing process which lowers the rate of MMHg degradation, causing a net decrease in MMHg photo-demethylation with increasing salinity. This competing process might involve quenching of singlet oxygen and DOM triplet excited states or radical scavenging by carbonate or halides (Buxton et al, 1988;Kong and Ferry, 2003;Brigante et al, 2010), which would increase with increasing salinity. However, additions of scavengers suggested singlet oxygen and hydroxyl radicals were not involved in the photo-demethylation we observed (see below).…”
Section: Salinitymentioning
confidence: 99%
“…The choice of 2-propanol as quencher was motivated by its elevated reactivity, as shown for instance by its reaction rate constant with • OH (2×10 9 M −1 s −1 ; Buxton et al, 1988). Although it is not the case of MCPA (vide infra), the excited states of some organic substrates are able to oxidise water to • OH, which is then involved into the direct phototransformation processes (Brigante et al, 2010). Accordingly, the ability of 2-propanol to effectively scavenge • OH would be potentially important in these studies.…”
Section: Laser Flash Photolysis Experimentsmentioning
confidence: 99%